2018
DOI: 10.1002/ptr.6020
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and herbal medicines: An unnecessary risk for women's health—A narrative review

Abstract: The indiscriminate use of herbal medicines to prevent or to heal diseases or even the use for questionable purposes such as weight loss has received both interest and scrutiny from the scientific community and general public alike. An increasing number of women put their own and the unborn child's health at risk due to a lack of knowledge about the phytochemical properties and adequate use of herbal medicine (phytomedicines or herbal supplements) and lack of communication with their healthcare provider. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 125 publications
0
33
0
4
Order By: Relevance
“…ADRs of herbal and traditional medicines are well known [80][81][82][83]. However, only 60.5% of HCPs considered it necessary to report events related to herbal drugs which is a concern (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…ADRs of herbal and traditional medicines are well known [80][81][82][83]. However, only 60.5% of HCPs considered it necessary to report events related to herbal drugs which is a concern (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Even though little is known about herbal medicines and risks of adverse effects, potential teratogenicity and interactions with medication, the pregnant women in our study considered herbal medicines less harmful compared with medication. These findings were most obvious in younger and lower educated women and it is a challenge for healthcare providers to give evidence‐based recommendations to these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some issues regarding herb-related genotoxicity have arisen. In particular, there are concerns about the frequent exposure of pregnant women and their foetuses to phytomedicines and herbal supplements without adequate knowledge of the safety during pregnancy [ 8 ]. An analysis of 14,551 births reported an increased risk of congenital malformations of the nervous system after exposure during the first trimester of pregnancy to Rhizoma Coptidis , a typical medicinal herb with the property of “clearing damp-heat” [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Swedish Medical Birth Register study reported that 787 of 860,215 women (0.9%) used herbal products during early pregnancy [ 6 ]. Accordingly, concerns about the potential risk for genotoxicity of herbal medicines and phytochemicals have arisen [ 7 , 8 ]. The Korean Ministry of Food and Drug Safety (MFDS) has developed a guideline (No.…”
Section: Introductionmentioning
confidence: 99%